HABITER SUR TRAJECTOIRE : UNE REFLEXION EN COURS DE ROUTE - Augustin IOAN; Ciprian MIHALI (Studia Universitatis Babeș-Bolyai. Philosophia, 2017)
This paper attempts to upgrade Deleuze and Guattari’s concept of nomadism to the contemporary work- and war-driven displacement of peoples in/to Europe. Starting from Augustin Ioan and his 2005 book Poverism, where he brought up the concept of living along trajectories (of migration), the two authors of the paper question the all-powerful status of place as envisioned by Heidegger at the conjunction between dwelling and being at home in one place. Along such trajectories that unite a point of departure and a tentative of arrival destination, contemporary migrants never leave their first home for good, nor do they ever arrive completely in a certain location. Even the alternative to displacement, the concept of homey feeling, was never studied outside the policies of major chain hotels, where it is provided a simulacra of arriving situations for frequent travelers.